2017
DOI: 10.1111/jth.13602
|View full text |Cite
|
Sign up to set email alerts
|

Eltrombopag, a thrombopoietin mimetic, crosses the blood–brain barrier and impairs iron‐dependent hippocampal neuron dendrite development

Abstract: Background Thrombocytopenia is common in sick neonates. Thrombopoietin mimetics (e.g., eltrombopag (ELT)) might provide an alternative therapy for selected neonates with severe and prolonged thrombocytopenia, and for infants and young children with different varieties of thrombocytopenia. However, ELT chelates intracellular iron, which may adversely affect developing organs with high metabolic requirements. Iron deficiency (ID) is particularly deleterious during brain development, impairing neuronal myelinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…Although we have not measured ELT entry into cells directly, we believe, based on several independent lines of evidence, that rapid cellular uptake of ELT is likely. First, ELT is taken up rapidly into isolated hepatocytes37 and neuronal cells 38. Second, studies with other chelators have shown that chelator entry into cells is key to cellular iron mobilization.…”
Section: Discussionmentioning
confidence: 99%
“…Although we have not measured ELT entry into cells directly, we believe, based on several independent lines of evidence, that rapid cellular uptake of ELT is likely. First, ELT is taken up rapidly into isolated hepatocytes37 and neuronal cells 38. Second, studies with other chelators have shown that chelator entry into cells is key to cellular iron mobilization.…”
Section: Discussionmentioning
confidence: 99%
“…Dendrites were traced using the NeuronJ plugin (http://www.imagescience.org/meijering/ software/neuronj/) as previously described. 5 Sholl analysis was performed on the NeuronJ tracings using the Sholl Analysis plugin (http://fiji.sc/Sholl_Analysis). For the Sholl analysis, the single animals were selected as the unit of analysis (5 animals per group).…”
Section: Sholl Analysismentioning
confidence: 99%
“…37 It has also been shown to have a significant impact on neonatal iron levels. 38 In children with chronic ITP, there has been some suggestion that use of eltrombopag may increase the risk of iron deficiency. 21 If iron deficiency develops and no other cause is identified, it may be appropriate to continue eltrombopag therapy and give iron supplementation, ensuring that the doses of the 2 medications are spaced as far apart as possible.…”
Section: February 2018mentioning
confidence: 99%